Illegal Latvia. Methods of intellectual property right enforcement in times of peer-to-peer file sharing - Sīlis, Georgs (Riga Graduate School of Law, 2018)
The paper is intended to provide an analytical understanding as to why Latvia is the top country in the world for the percentage of the internet population that are considered pirates, i.e., internet users who acquire copyright protected works (music, audiovisual, and software) from unlawful sources, such as peer-to-peer (P2P) networks (torrents), streaming and direct downloads, and what in turn can be done to combat this in lieu of Court of Justice of the European Union of June 2017 judgment in Stichting Brein v Ziggo BV and XS4All Internet BV, which finally gave a European-Union-wide (EU) ruling on whether torrent websites violate copyright law in the sense of “communication to the public” - an exclusive right of copyright holders as defined by the Information Society Directive of 2001. The court ruled that torrent websites do indeed violate copyright law and as such an injunction against internet service providers (ISPs) is proportionate to the goals of high copyright protection goals that the EU set in the Information Society Directive.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Copyright law